Bunions - Ferrari, Jill (BMJ Publishing Group, 2009)
INTRODUCTION: Bunions are prominent and often inflamed metatarsal heads and overlying bursae, usually associated with hallux valgus, where the great toe moves towards the second toe. Hallux valgus is found in at least 2% of children aged 9 to 10 years, and almost half of adults, with greater prevalence in women. METHODS AND OUTCOMES: We conducted a systematic review and aimed to answer the following clinical questions: What are the effects of conservative treatments, surgery, and postoperative care for bunions? We searched: Medline, Embase, The Cochrane Library, and other important databases up to May 2008 (Clinical Evidence reviews are updated periodically; please check our website for the most up-to-date version of this review). We included harms alerts from relevant organisations such as the US Food and Drug Administration (FDA) and the UK Medicines and Healthcare products Regulatory Agency (MHRA). RESULTS: We found 21 systematic reviews, RCTs, or observational studies that met our inclusion criteria. We performed a GRADE evaluation of the quality of evidence for interventions. CONCLUSIONS: In this systematic review, we present information relating to the effectiveness and safety of the following interventions: arthrodesis (Lapidus procedure); bone fixation (absorbable pin fixation, percutaneous Kirschner-wire fixation, screw fixation plus early mobilisation [early weight-bearing], standard fixation, suture fixation plus immobilisation [delayed weight-bearing]); chevron osteotomy plus adductor tenotomy; distal metatarsal osteotomy; early weight-bearing; Keller’s arthroplasty; Keller–Lelievre arthroplasty; night splints; orthoses (including antipronatory orthoses in children); phalangeal (Akin) osteotomy plus distal chevron osteotomy; proximal osteotomy, and slipper casts.